Decoding the anti-Leishmania braziliensis activity of 1,10-phenanthroline-5,6-dione and its silver- and copper-based complexes: In vitro and in vivo approaches - André L.S. Santos; Ana Karina C. Lima; Simone S.C. Oliveira; Rosiane F. dos Santos; Michael Devereux; Malachy McCann; Marta H. Branquinha; Patrícia M.L. Dutra (European Journal of Medicinal Chemistry Reports, 2022)
Leishmaniasis is a neglected tropical disease, whose chemotherapy still presents a series of severe side effects for the patient. Recently, our group published the leishmanicidal action of 1,10-phenanthroline (1), 1,10-phenanthroline-5,6-dione (phendione, 2) and its silver(I) [Ag(phendione)2]ClO4 (3) and copper(II) [Cu(phendione)3](ClO4)2.4H2O (4) complexes against Leishmania braziliensis. Herein, we deciphered the mechanisms of anti-L. braziliensis action of these promising compounds. The IC50 values were calculated for L. braziliensis promastigotes and the potency order was: 4 (0.5 ​μM) ​> ​3 (6.1 ​μM) ​> ​2 (21.3 ​μM) ​> ​1 (32.7 ​μM). Treatment of promastigotes with test compounds induced mitochondrial dysfunction with concomitant increment in the production of intracellular reactive oxygen species, culminating in parasite death by apoptosis as judged by the increased percentage of annexin-positive/propidium iodide-negative parasites and DNA cleavage (classical phenotypic markers of apoptotic cells). Subsequently, the effects of these test compounds on in vitro interaction between L. braziliensis and hamster macrophages showed a significant reduction in the number of intracellular amastigotes, and consequently parasite death by apoptosis. The test compounds presented a protective action in in vivo hamster infections without presenting toxicity to the mammalian host. The compounds limited the development of the paw lesion in hamsters infected with L. braziliensis as well as drastically reducing the number of parasites in both infected paw and lymph nodes draining the lesion, with 4 being the most effective compound. Collectively, our results emphasize the high potential of metal-based compounds, particularly 4, as new, safe and effective alternatives for the treatment of L. braziliensis infection.